Pengaruh Disiplin Kerja dan Komitmen terhadap Etos Kerja Karyawan PT Panjunan Tasikmalaya - Delik Iskandar; Enas Enas; Apri Budianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The problems faced in this study include (1) How does work discipline affect the work ethic of PT Panjunan Tasikmalaya employees? (2) How does commitment affect the work ethic of PT Panjunan Tasikmalaya employees? (3) How do work discipline and commitment affect the work ethic of PT Panjunan Tasikmalaya employees? This study aims to study, find out, and analyze (1) The effect of work discipline on the work ethic of PT Panjunan Tasikmalaya employees. (2) The effect of commitment on the work ethic of PT Panjunan Tasikmalaya employees. (3) The effect of work discipline and commitment on the work ethic of PT Panjunan Tasikmalaya employees. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression (Multiple Regression). The results of the study inform that (1) Discipline at PT. Panjunan Tasikmalaya is very high. With the highest value on the responsibility indicator and the lowest value on the obedience indicator. Discipline has a positive effect on employee work ethic at PT. Panjunan Tasikmalaya. This means that if discipline is increased, then employee work ethic at PT. Panjunan Tasikmalaya will also increase. (2) Commitment at PT. Panjunan Tasikmalaya is high. With the highest value on the sense of belonging indicator (sense of belonging) and the lowest value on the sense of passion for work indicator. Commitment has a positive effect on employee work ethic at PT. Panjunan Tasikmalaya. This means that if commitment is increased, then employee work ethic at PT. Panjunan Tasikmalaya will also increase. (3) Employee work ethic at PT. Panjunan Tasikmalaya is very high. With the highest value on the indicator of interpersonal skills and the lowest value on the indicator of reliability.